Critical illness insurance in life cycle portfolio problems - Lorenz S. Schendel (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
I analyze a critical illness insurance in a consumption-investment model over the life cycle. I solve a model with stochastic mortality risk and health shock risk numerically. These shocks are interpreted as critical illness and can negatively affect the expected remaining lifetime, the health expenses, and the income. In order to hedge the health expense effect of a shock, the agent has the possibility to contract a critical illness insurance. My results highlight that the critical illness insurance is strongly desired by the agents. With an insurance profit of 20%, nearly all agents contract the insurance in the working stage of the life cycle and more than 50% of the agents contract the insurance during retirement. With an insurance profit of 200%, still nearly all working agents contract the insurance, whereas there is little demand in the retirement stage.
Keywords: D91; G11; I13; 330; Health shocks; Health expenses; Labor income risk; Stochastic mortality risk; Portfolio choice